Managing the transition from tradition to innovation for the Heidelberg/Heilbronn Medical Informatics Master of Science program - Knaup-Gregori, Petra; Bendl, Rolf; Eisenmann, Urs; Hastenteufel, Mark; Reichenbach, Alexandra (Applied clinical informatics, 2025)
Background: To keep pace with the developments in the medical informatics field, the curriculum of the Heidelberg/Heilbronn Medical Informatics Master of Science program is continuously updated. In its latest revision we restructured our master's program to allow more flexibility to accommodate updates and include current topics and to enable students' choices. Objectives: This study aimed to present our new concepts for graduate medical informatics education, share our experiences, and provide insights into the perception of these concepts by advanced students and graduates. Methods: Our new curriculum consists of three core components: Areas of concentration that bundle elective courses in an important domain of medical informatics, a large catalog of elective courses, and introductory/alignment courses for students without a bachelor's degree in medical informatics. We conducted an online survey of graduates and students with at least 75 credits to assess their opinion on the program's effectiveness and attractiveness. Results: Mandatory courses include clinical medicine, project management, research, and practical training in biomedical informatics. Five areas of concentration bundle elective courses for 30 credits to provide a solid foundation in an important domain in medical informatics. These are bioinformatics, data science, computer-aided diagnosis and therapy systems, information management, and software engineering in medicine. The catalog of electives offers a total of 67 courses. About 75% of the courses are assigned to more than one area of concentration. Our survey demonstrates that the participants highly appreciate the flexibility of the electives and the opportunity to develop an area of expertise. Conclusion: Offering a high degree of flexibility to our students has motivated them to join our program and resulted in a high level of student satisfaction. By designing the curriculum with areas of concentration and providing an infrastructure that permits courses on emerging topics to be added easily to the curriculum, we were able to meet our students' expectations.